PTH-006 Repeat bi-directional endoscopy for recurrent iron deficiency anaemia – is it worth it?. (17th June 2017) - Rej, A; Al-Talib, I; Hebden, JM
Abstract : Introduction: The BSG guidelines for iron deficiency anaemia (IDA) advise investigation with bi-directional endoscopy, with imaging of the small bowel reserved for patients failing to respond to iron or patients with a recurrence of anaemia within 2 years and failing to respond to iron. There is no guidance on when repeat endoscopic investigation should be considered. Method: We searched our endoscopic database for patients who had undergone repeat bi-directional endoscopy for the indication 'anaemia' over the last 12 years (2005–2016). Diagnoses at index and repeat endoscopies were compared. Significant findings accountable for recurrent anaemia were classified as: carcinoma; polyp >1.5 cm; ulcer >1 cm; angiodysplasia >5/requiring APC; severe oesophagitis (LA grade C/D); coeliac disease. Results: 232 patients (median age 66 [range 38–84]; 120 female) were identified. Findings responsible for anaemia at index investigation were noted in 16 (6.9%) patients at gastroscopy and 24 (10.3%) patients at colonoscopy (see Table 1). Repeat investigations were performed at a median of 41 months (range 3–106). Findings accounting for anaemia on repeat investigation were detected in 12 (5.2%) patients at gastroscopy (1 angiodysplasia was also present at index) and 10 (4.3%) patients at colonoscopy (3 out of 4 with angiodysplasia were present at index; 1 was a recurrence of malignancy). Thus, new findings occurred in 11 (4.7%) patients at gastroscopy, and 7 (3.0%) patients at colonoscopy. Three gastric carcinomas arose 19, 20 and 52 months after initial gastroscopy (one was a GOJ carcinoma arising in an index case of Barrett's oesophagus). The 2 colorectal carcinomas occurred 20 and 41 months (the former a recurrence) after index colonoscopy (bowel preparation was adequate in both initial colonoscopies). Conclusion: The findings suggest a small but significant yield from repeat bi-directional endoscopy in recurrent anaemia, with malignancy being identified in 1.3% at repeat gastroscopy and 0.9% at repeat colonoscopy. Reference: 1. Goddard AF, James MW, McIntyre AS, et al. Guidelines for the management of iron deficiency anaemia. Gut2011;60:1309–16. Disclosure of Interest: None Declared